2007
DOI: 10.1128/iai.00260-07
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Specificity and Autoimmunity Are Distinct Features of Antigen-Driven Immune Responses in Neuroborreliosis

Abstract: Neuroborreliosis (NB) is a chronic infectious disease of the central nervous system (CNS) caused by a tick-borne spirochete, Borrelia burgdorferi. In addition to direct effects of the causative infectious agent, additional immunity-mediated mechanisms are thought to play a role in the CNS pathology of NB. In order to further understand the involvement of humoral immune mechanisms in NB, we dissected the intrathecal antibody responses down to the single-plasma-cell level. Starting with single-cell reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…Myelin reactivity of MS-mAb appeared independent of the disease course and treatment, and could even be found in a patient with optic neuritis (CIS1), which is deemed to be a very early form of MS. While this finding fits the generally accepted hypothesis of MS being a demyelinating autoimmune disease involving potentially pathogenic humoral immune responses, recent data from our laboratory suggest that the myelin reactivity shown in the current study is not specific for MS: Antibodies from cePC from the CSF of a patient with neuroborreliosis included reactivities with Borrelia burgdorferi, the causative pathogen, but also with CNS myelin [26].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Myelin reactivity of MS-mAb appeared independent of the disease course and treatment, and could even be found in a patient with optic neuritis (CIS1), which is deemed to be a very early form of MS. While this finding fits the generally accepted hypothesis of MS being a demyelinating autoimmune disease involving potentially pathogenic humoral immune responses, recent data from our laboratory suggest that the myelin reactivity shown in the current study is not specific for MS: Antibodies from cePC from the CSF of a patient with neuroborreliosis included reactivities with Borrelia burgdorferi, the causative pathogen, but also with CNS myelin [26].…”
Section: Discussionmentioning
confidence: 50%
“…PCR-amplified Ig H and L chain genes from each plasma cell clone were used to recombinantly reconstruct the antigen specificity of antibodies expressed by cePC preserving the original Ig H and L chain pairings of individual plasma cells. This approach has been demonstrated to faithfully resurrect pathogen-specific antibodies from individual plasma cells from patients with subacute sclerosing panencephalitis [25] and borreliosis, and to maintain the original antibody affinity [26].…”
Section: Clonally Expanded Plasma Cells In the Csf Of Ms Patientsmentioning
confidence: 99%
“…All four treatment‐naive patients with recent onset anti‐NMDAR encephalitis in the current study showed intrathecal B‐cell and plasma cell accumulation and intrathecal production of NMDAR‐specific IgG. Moreover, using single‐cell RT‐PCR of FACS‐sorted CD138 + CSF plasma cells and recombinant antibody technology,19, 21 we identified expanded clones and were able to obtain seven different rhuMab (SSM1‐7) from intrathecal cePc of one of the anti‐NMDAR encephalitis patients. Ig sequences showed varying numbers of mutations from published germline sequences, indicating antigen‐driven expansion and ongoing somatic hypermutations.…”
Section: Discussionmentioning
confidence: 60%
“…To elucidate whether cePc are the actual source of the intrathecal autoantibody response, we cloned paired immunoglobulin heavy‐ and light‐chain variable gene regions from cePc essentially as previously described 19, 21. PEI mediated cotransfection of IgG‐HC and matching Ig‐LC expression vectors into FreeStyle 293‐F cells were carried out to produce recombinant monoclonal antibodies in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation